A solidão da mulher negra: sua subjetividade e seu preterimento pelo homem negro na cidade de São Paulo - Souza, Claudete Alves da Silva (2008)
This work has as an aim to tackle the loneliness of the black woman in the affectivesexual dimension, having as a central axis her rejection while pretender to the marriage market by the partner of the same ethnicity. For the understanding of this phenomenon we looked for in the literature datas that could show this empirical fact starting from the socio-historical conception of this subject and the correlated implications. Thus, in addition to the Bibliographic research, the methodological line leds up qualitative technical piece, characterized by the focus group and by the analysis of the speech, allowing to know the representations of these women. The obtained datas with the devolution of 62 interview routes sent to 62 women guided the focus group realization. The datas analysis showed that women who joined the survey consider that there is a disadvantage situation of the black women compared to the white women regarding to the preference of the black men in the choice of the affective and conjugal partner. This situation affects more intensively on young black women, independent of the social class. The behavior of the black man was perceived as a result of a social devaluation of the black population from Brazil, from a long time ago, that is stimulating the young black men to seek "lighten" the family. The Inter-racial association was seen as beneficial to the black man, meaning its social climbing and very disadvantaged for the black woman, by the tendency observed between the inter-racials couples the couple black man-white woman as predominant. The participants believe that the exclusion of the black woman brings loneliness and humiliation. To face this situation, the group considered that the formal education is a rescue major factor of the black ethnic black, enabling the identification of a bigger number of people with thesevalues